The Novel Functions of M4 Muscarinic Receptors - Myslivecek, J; Janisova, K (Physiological research, 2025)
The role of M4 muscarinic receptors in locomotor activity regulation remains controversial, with conflicting findings hampering our understanding of movement disorders. This uncertainty is further complicated by the unexplored relationship between M4 receptors and biological rhythms, as well as potential sex-specific effects that may explain previous inconsistent results. Through systematic investigation of locomotor functions in biological rhythm paradigms, we discovered that M4 muscarinic receptors significantly modulate locomotor activity rhythms via brain pacemaker mechanisms. Notably, this regulatory effect displayed marked sexual dimorphism, being present exclusively in females, suggesting crucial interactions with sex hormones. Our research identified the striatum as the key structure directing these locomotor biological rhythms. These findings provide critical insights into the sex-specific nature of M4 receptor function and establish a new framework for understanding hyperactivity disorders, particularly those exhibiting sex-based differences in prevalence or manifestation. Key words M4 muscarinic receptors " M1 muscarinic receptors " Biological rhythm " Locomotor activity " Striatum.
Keywords: myši inbrední C57BL; charakteristické znaky pohlaví; Mice; Corpus Striatum; lokomoce; Male; Locomotion; corpus striatum; ženské pohlaví; Mice, Inbred C57BL; myši; Animals; receptor muskarinový M4; Sex Characteristics; mužské pohlaví; zvířata; Female; Receptor, Muscarinic M4